Design a stream deck by using microcontroller - Chai, Chun Wei (2023)

(untitled)
Nowadays, stream deck is a very well-liked application for streamers or editors. It is designed to automate basic actions like switching sceneries and going live, but the same platform is helpful even if you don't play games for an audience. For instance, copying and pasting for editors, opening a file with a single click (recorded the keystroke and macro), and other features. Due to pandemic situation, most of the workers is going to work from home while some workers are lost their jobs, and there is keep borning out new generation, they would like to touch more new technology items. However, stream deck is a good tool to conduct their job easier especially for streamers, editors, teacher, programmers and so on. Therefore, stream deck is being developed by plenty of companies recently. In order to carry out this project, a PCB is necessary. A PCB is built to combine all hardware and become a system. A 3D printer is necessary to build for a casing for stream deck. A webserver is constructed to act as user interface for users to change their configuration. Moreover, ESP32 is act as a “heart” or “brain” that communicate with TFT screen while the program code for the module will be written and compiled by using programming IDE software. The main function of the stream deck is to create a shortcut key into a key to do a specific task. After the configuration or setup is done, the LED touch screen- ILI9488 TFT screen with XPT2046 touch controller will show up the options on the screen. At the end of this project, a DIY stream deck system is to create 6 buttons to let users to choose their option to conduct specific task by settings up the programmable buttons.